2016
DOI: 10.1002/qj.2877
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of a continental night‐time stratocumulus‐topped boundary layer to varying environmental conditions

Abstract: Large‐eddy simulation of a nocturnal stratocumulus‐topped boundary layer in a continental midlatitude environment has been performed to examine the sensitivity of the cloud to a number of different environmental parameters. The simulations showed that the stratocumulus cloud was strongly affected by the presence of an overlying free tropospheric cirrus cloud (FTC), in agreement with previous studies of marine nighttime stratocumulus. When introducing an FTC with an optical thickness of 2, stratocumulus liquid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 83 publications
(100 reference statements)
0
4
0
Order By: Relevance
“…The LLJ, which is linked to the north-south pressure gradient associated with the Saharan heat low (Parker et al, 2005;Lothon et al, 2008;Abdou et al, 2010), occurs frequently in this region and is found approximately in the same layer as the LLCs. It is unclear what role middle and upper-level clouds play in nocturnal cloud formation, their morning dissolution and in the growth of the cloud-topped daytime boundary layer in the following day (Leung et al, 2016). Aerosols, mainly emitted from the urban agglomerations along the West African coast, and their north-eastward transport with the monsoon flow, are also suspected to impact cloud characteristics in southern West Africa (Knippertz et al, 2015a).…”
Section: Introductionmentioning
confidence: 99%
“…The LLJ, which is linked to the north-south pressure gradient associated with the Saharan heat low (Parker et al, 2005;Lothon et al, 2008;Abdou et al, 2010), occurs frequently in this region and is found approximately in the same layer as the LLCs. It is unclear what role middle and upper-level clouds play in nocturnal cloud formation, their morning dissolution and in the growth of the cloud-topped daytime boundary layer in the following day (Leung et al, 2016). Aerosols, mainly emitted from the urban agglomerations along the West African coast, and their north-eastward transport with the monsoon flow, are also suspected to impact cloud characteristics in southern West Africa (Knippertz et al, 2015a).…”
Section: Introductionmentioning
confidence: 99%
“…With respect to the latter process, shear-induced turbulence in the upper part of the LLJ and in the lower part of the African Easterly Jet (AEJ) could, depending on the position of the AEJ, mix the wet monsoon flow and the dry Saharan air layer above. Prior to DACCIWA it was not clear to what extent the nocturnal LLSC formation, their morning dissolution and the growth of the cloud-topped daytime ABL on the following day depend on free tropospheric moisture content and middle and upper-level clouds 10 , 11 . Aerosols emitted from the main metropolitan areas on the Gulf of Guinea coastline (Abidjan, Accra and, Lagos) and advected by the south-westerly monsoon flow also influence LLSC macro-physical characteristics in southern West Africa by affecting cloud microphysical properties such as cloud droplet and ice crystal formation and size-distribution 3 , 12 .…”
Section: Background and Summarymentioning
confidence: 99%
“…from biogenic sources, and a general increase in particle size which can also likely be attributed to condensation of semi-and non-volatile biogenic compounds on pre-existing particles. Over the boreal region, biogenic compounds do have a significant effect on the aerosol load during the warm months, and their emissions increase with increasing temperature (Liao et al, 2014). Overall, an increase in the biogenic contribution, decrease in the anthropogenic contribution (BC), and ageing of long-range BC increase the scavenging efficiency of scattering material.…”
Section: Impact Of Air Temperaturementioning
confidence: 99%